2004
DOI: 10.1007/s00203-004-0699-8
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Hmp, an ?oxygen-binding flavohaemoprotein?, produces superoxide anion and self-destructs

Abstract: Escherichia coli Hmp is a homologue of Ralstonia eutropha FHP, the first reported bacterial flavohaemoglobin, and functions in NO detoxification. Photolysis of CO-ligated Hmp in the presence of oxygen gave a photodissociable oxy species with k(on) 2.82x10(7) M(-1) s(-1) and k(off) 4.49x10(3) s(-1). The dissociation constant of the primary O(2) compound was 160 microM (25 degrees C, pH 7.0). In order to detect superoxide formation, ferric horseradish peroxidase was used. Hmp formed the oxy compound within milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…It has been shown that E. coli Hmp is irreversibly inactivated in the presence of O 2 and NADH due to superoxide formed during turnover. However, in the presence of NO, superoxide production is abolished (40). Thus, we speculate that a small amount of NO induces hmp expression and protects the flavohemoglobin from self-destruction.…”
Section: Resultsmentioning
confidence: 75%
“…It has been shown that E. coli Hmp is irreversibly inactivated in the presence of O 2 and NADH due to superoxide formed during turnover. However, in the presence of NO, superoxide production is abolished (40). Thus, we speculate that a small amount of NO induces hmp expression and protects the flavohemoglobin from self-destruction.…”
Section: Resultsmentioning
confidence: 75%
“…This hypothesis is supported by the ability of several flavin-containing proteins to generate superoxide upon oneelectron oxidation by dioxygen (10). Also, it was previously shown that NAD(P)H is oxidized by flavohemoglobin with the electrons transferred via FAD to external acceptors when the ferrous heme is blocked (28).…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that, under certain conditions, E. coli flavohemoglobin produces superoxide ions (16,28). To investigate the effect of antibiotic binding to flavohemoglobin on radical formation, we used the spin trap BMPO in EPR experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Under aerobic conditions and in the absence of NO, Hmp forms the highly reactive species O { : 2 via the reduction of molecular oxygen (Membrillo-Hernández et al, 1996;Orii et al, 1992;Wu et al, 2004); however, in the presence of NO, the relatively inert nitrate ion is formed in a denitrosylase or dioxygenase reaction (Gardner et al, 2000;Hausladen et al, 2001;Poole & Hughes, 2000). As Hmp levels are elevated in an nsrR mutant (Fig.…”
Section: No Rescues An Nsrr Mutant From Peroxynitrite Hypersensitivitymentioning
confidence: 99%
“…Aerobically, Hmp catalyses the reaction between oxygen and NO to produce relatively inert nitrate (Gardner et al, 1998;Hausladen et al, 1998). In the absence of NO, O { : 2 is formed, which reacts with a variety of compounds leading to the formation of other oxidative stresses such as hydrogen peroxide (H 2 O 2 ) (MembrilloHernández et al, 1996;Orii et al, 1992;Wu et al, 2004). Anaerobically, NO reacts with the haem of Hmp to yield a nitrosyl anion with subsequent formation of nitrous oxide (Hausladen et al, 1998;Kim et al, 1999;Liu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%